Long-term PM2.5 exposure and sepsis mortality in a US medicare cohort. - Honda, Trenton J.; Kazemiparkouhi, Fatemeh.; Henry, Trenton D.; Suh, Helen H. (Tufts University. Tisch Library., 2022)
Keywords: Sepsis, Air pollution, Chronic exposure, Particulate matter.; Springer Open.